PERKEMBANGAN BONDING DALAM KEMAJUAN RESTORASI ESTETIK - Dwi Kartika Apriyono (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2010)
There has been dramatic progression in the adhesion of dental adhesives and resins to enamel and dentin in the 40 years since Buonocore1 introduced the technique of etching enamel with phosphoric acid to improve adhesion to enamel. The first dental adhesives bonded resins to enamel only, with little or no dentin adhesion. Subsequent generations have dramatically improved bond strength to dentin and the sealing of dentin margins while retaining a strong bond to enamel. The widespread demand for, and use of, dental adhesives has fuelled an intensive development of better and easier dental adhesives in rapid succession; dentists have literally been inundated with successive “generations” of adhesive materials. There are seven generatios in bonding agent and have a different characteristics. This article discusses the progression of dental adhesives up to the last generation.